2009
DOI: 10.17221/24/2008-rae
|View full text |Cite
|
Sign up to set email alerts
|

Effect of abrasive particle size on abrasive wear of hardfacing alloys

Abstract: Abstract:Hardfacing is one of the most useful and economical ways to improve the performance of components submitted to severe wear conditions. This study has been made for the comparison of microstructure and abrasion resistance of hardfacing alloys reinforced with chromium carbides or complex carbides. The hardfacing alloys were deposited onto ČNS EN S235JR low carbon steel plates by the gas metal arc welding (GMAW) method. Different commercial hardfacing electrodes were applied to investigate the effect of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 20 publications
0
21
0
Order By: Relevance
“…Figure 5 shows the micro-hardness of the abrasives and the composite phases. The wear resistance of the composites has a direct relationship with the hardness, the load and the second phases [27]. It can be known that the hardness of ZTA particles is higher than that of the abrasives (Al2O3, SiO2, and Fe2O3) but lower than that of the SiC.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…Figure 5 shows the micro-hardness of the abrasives and the composite phases. The wear resistance of the composites has a direct relationship with the hardness, the load and the second phases [27]. It can be known that the hardness of ZTA particles is higher than that of the abrasives (Al2O3, SiO2, and Fe2O3) but lower than that of the SiC.…”
Section: Characterization Methodsmentioning
confidence: 99%
“…The niobium element in alloy 2 helps to enrich the chromium in matrix which increases the austenite formation temperature and forms austenite matrix. The formation of reinforced NbC in alloy 2 helps prevent the detachment of chromium-rich M 7 C 3 primary carbides [35,39].…”
Section: Methodsmentioning
confidence: 99%
“…According to Dolman [22], a hypereutectic hardfacing with 30 -60% volume of M7C3 carbides in a ferrous matrix (M = Cr, Fe, Mn) gave a nominal hardness of M7C3 carbides of 1200 -1500HV and 600 -700HV for the ferrous matrix. More so, Chotĕborský et al [43] revealed that the hardness of hypereutectic hardfacing increases with the increasing proportions of carbide phases MC and M7C3. Coronado et al [34], showed that hardfacing using flux cored arc welding gives better wear resistance than hardfacing by shielded metal arc welding.…”
Section: Hardness Of Hardfacings and Wear Hardness Of Hardfacings Andmentioning
confidence: 99%